An updated circumscription of Saussurea (Cardueae, Asteraceae) and allied genera based on morphological and molecular data - Kasana, Shruti; Dwivedi, Mayank D.; Uniyal, Prem L.; Pandey, Arun K. (Phytotaxa, 2020)
The temperate Asteraceae genus Saussurea displays much morphological variation. Recent and previous taxonomic revisions have led to redefinition and later lumping of several additional genera. This study made use of morphological and molecular data to answer questions related to smaller split genera from Saussurea. The result indicates that the genus Lipschitziella, split from Saussurea, is monophyletic after the inclusion of Himalaiella. Another closely allied genus Dolomiaea is also recovered monophyletic after the inclusion of Saussurea costus and Frolovia frolowii. Nine possible new combinations are established.